Oligometastatic breast cancer: A mini review - Sameer Rastogi; Seema Gulia; Jyoti Bajpai; Jaya Ghosh; Sudeep Gupta (Indian Journal of Medical and Paediatric Oncology)
With few exceptions such as germ cell tumors, trophoblastic neoplasms and colonic cancers, metastatic solid tumors are considered largely incurable. It is increasingly appreciated that oligometaststic cancer differs from multi-metastatic disease in prognosis and survival. Oligometastatic breast cancer (OMBC) is, therefore, sometimes considered as an intermediate biological state between localized and widely metastatic disease. There is no strict definition of OMBC with studies using different criteria. Treatment of OMBC is still controversial in view of sparse data that is retrospective. However, there is an increasing shift toward individualized, multidisciplinary management of OMBC with the intent to cure some patients. This article will concisely review the subject of OMBC from points of view of biology and practical management recommendations.